Efektivitas Bimbingan Klasikal Berbasis Pelatihan Growth Mindset dan Distress Tolerance Untuk Meningkatkan Kualitas Hidup Mahasiswa - Mila Dwi Kania; Anandha Putri Rahimsyah; Feida Noorlaila Isti'adah; Gian Sugiana Sugara (Indonesian Journal of Educational Counseling, 2026)
The college period is an important transitional phase that requires students to adapt to complex academic, social, and emotional challenges. Difficulties in adaptation often reduce students' well-being and quality of life. This study aims to analyze the effectiveness of classical guidance services based on growth mindset and distress tolerance training in improving students' quality of life. The method used is a quantitative approach with a One-Group Pretest-Posttest design. The research sample consisted of 30 students selected through purposive sampling. The data collection instrument used the Quality of Life Inventory (QOLI), and the analysis was performed using a paired sample t-test. The results of the study showed a significant increase in students' quality of life scores after participating in the training, both overall and in each dimension. These findings confirm that the integration of growth mindset and distress tolerance can strengthen students' cognitive and emotional aspects, thereby improving their psychological well-being and ability to adapt to academic pressure.